Hypoglycemic Potentials of Newbouldia laevis Stem Bark Extract in Alloxan-Induced Diabetic Rats - Umaru, Isaac John; Chisom, Gabriel Favour; Umaru, Kerenhappuch Isaac; Tansaba, Akafa Andes; Nanmar, Chakfa; Ugoeze, Egeonu Stephen (African Journal of Biochemistry and Molecular Biology Research, 2024)
This study was carried out to investigate the antidiabetic of the methanol extract of Newbouldia stem bark and to determine its safety and toxicity. Alloxan (150 mg/kg) was administered to albino rats via the oral route. The diabetic rats were then placed in 6 groups, following stabilization of hyperglycemia. The first group was non-diabetic, the second and third group were the diabetic control. The next three groups received, each day, 100, 200 and 400 mg/kg body weight of the methanol extract Newbouldia laevis and the second group received a reference standard, metformin (200mg/kg). Treatment was via the oral route for 14 days and fasting blood sugar level was monitored over this period. Acute toxicity (oral and intraperitoneal) studies on the extract was carried out. Blood glucose levels from day 1 to 14 days of treatment increased significantly (p <0.05) in all the treatment groups, except group 3 (positive control) which showed no significant difference compared to the normal control group. This study supports the use of Newbouldia laevis in traditional medicine as well as highlights the need to further explore the potentials of the plant extract as an antidiabetic.